2015
DOI: 10.14314/polimery.2015.644
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of computer model for polymer plastication process in injection molding

Abstract: This paper is a continuation of the work on a comprehensive model of the plastication process in injection molding. The aim of this research is the analysis of the results generated by the proposed model by comparing these results with the wide experimental characteristics of real plasticating system of injection molding machine for two polymers-PE-LD and PE-HD, differing in rheological and thermal properties due to the different physical structure of both polymers. It was found that the model correctly determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…It consists of a dynamic extrusion melting model for the rotation period, a transient heat conduction model with a phase transition for the screw rest period, and a model for the drifting of the beginning of melting during the injection cycle. Later, the basic research in this field was performed first by Potente et al [136,137], and then by Steller et al [138,139] as well as by Covas et al [140]. Recently, Wilczyński et al [141] performed experimental studies on the melting mechanism of polymers in injection molding machines.…”
Section: Melting Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of a dynamic extrusion melting model for the rotation period, a transient heat conduction model with a phase transition for the screw rest period, and a model for the drifting of the beginning of melting during the injection cycle. Later, the basic research in this field was performed first by Potente et al [136,137], and then by Steller et al [138,139] as well as by Covas et al [140]. Recently, Wilczyński et al [141] performed experimental studies on the melting mechanism of polymers in injection molding machines.…”
Section: Melting Sectionmentioning
confidence: 99%
“…It has been observed that melting in the injection molding machine occurs to some extent, according to the Tadmor mechanism, with clearly visible starvation (Figure 8). The existing models of the injection molding process (plasticating unit) [136][137][138][139][140] differ from the extrusion models in that they involve the static and dynamic phases of melting (stationary and rotating screw) with an axial screw movement. However, it is assumed that the screw is fully filled with a material such as in the flood fed extrusion (Figure 2), which is inconsistent with Figure 8 where starvation is clearly seen in the starve fed extrusion (Figure 4).…”
Section: Melting Sectionmentioning
confidence: 99%
“…It relies on using mathematical models for the plasticization process on the basis of the law of mass, momentum and energy conservation and the characteristics of a material. The models join the output characteristics of the plasticization process, such as pressure and temperature distribution, throughput, power demand and so forth, with the geometry of the plasticizing system, the adjustable process parameters and the material data, allowing thereby the optimization of the equipment design [1].…”
Section: Introductionmentioning
confidence: 99%
“…Another comprehensive model of the plasticization process in the injection moulding which reflects well the dynamics of a real reciprocating screw was presented in [44,45]. More details of this model were published in [1,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…This reciprocating plastication process is affected by various molding conditions such as the screw design, cylinder temperature, rotation speed, back pressure, and cycle time . The cylinder internal pressure, torque, resin‐melting situation, and other factors affecting non‐reinforced resins have been predicted in simulation models of the resin‐melting process . Tatsuno and co‐workers also conducted visualization experiments of the reciprocating plastication processes of various unreinforced resins, but without considering the relationship between the reciprocating plastication of L‐GFPP and the fiber‐length distribution in the resin.…”
Section: Introductionmentioning
confidence: 99%